Writing Emotions Theoretical Concepts and Selected Case Studies in Literature - Jandl, Ingeborg; Knaller, Susanne; Schönfellner, Sabine (Lettre, 2017)
After a long period of neglect, emotions have become an important topic within literary studies. This collection of essays stresses the complex link between aesthetic and non-aesthetic emotional components. Against this background, emotional patterns are discussed by focusing on the practice of writing as well as on the impact of emotional patterns on receptive processes. Readers will be confronted with a concept of aesthetic emotions as formative both within the writing and the reading process. Essays, ranging in matter from the beginning of modern drama to digital formats and theoretical questions, discuss examples from English, German, French, Russian and American literature.